1998
DOI: 10.1242/dev.125.14.2599
|View full text |Cite
|
Sign up to set email alerts
|

Vax1is a novel homeobox-containing gene expressed in the developing anterior ventral forebrain

Abstract: The vertebrate forebrain is formed at the rostral end of the neural plate under the regulation of local and specific signals emanating from both the endomesoderm and neuroectoderm. The development of the rostral and ventral forebrain in particular was difficult to study, mainly because no specific markers are available to date. Here, we report the identification of Vax1, a novel homeobox-containing gene identified in mouse, Xenopus and human. It is closely related to members of the Not and Emx gene families, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(9 citation statements)
references
References 84 publications
1
8
0
Order By: Relevance
“…Similarly, PRKX seemed to determine the upregulation of DMBX1, which is expressed in the urogenital system and testis [74], as well as the positive modulation of VAX1 in VK2 E6/E7 cells. VAX1 interacts with EMX2 protein [75], which was found to be indispensable for the formation of both MD and WD in mice [76]. Moreover, in our study, ectopic PRKX overexpression seemed to upregulate HOXD13, whose alteration has been linked to syndromes affecting genitourinary development [77], renal agenesis [78], and limb malformations such as synpolydactyly and polydactyly [79].…”
Section: Discussionsupporting
confidence: 53%
“…Similarly, PRKX seemed to determine the upregulation of DMBX1, which is expressed in the urogenital system and testis [74], as well as the positive modulation of VAX1 in VK2 E6/E7 cells. VAX1 interacts with EMX2 protein [75], which was found to be indispensable for the formation of both MD and WD in mice [76]. Moreover, in our study, ectopic PRKX overexpression seemed to upregulate HOXD13, whose alteration has been linked to syndromes affecting genitourinary development [77], renal agenesis [78], and limb malformations such as synpolydactyly and polydactyly [79].…”
Section: Discussionsupporting
confidence: 53%
“…Vax1 was a crucial gene for the development of the basal forebrain and visual system in animal experiments, and it also participated in the rostral formation of vertebrates. 17 Slavotinek et al reported that Vax1 mutation is associated with human cleft lip and palate, absence of the pineal gland, corpus callosum agenesis, hippocampal malformations and small optic nerves. 18 …”
Section: Discussionmentioning
confidence: 99%
“…LHX6 , GAD1 , GAD2 , DLX2 , DLX5, and NEUROD2 and NEUROD6 , which are regulators expressed in late‐stage progenitors and neurons, and are required for distinct neuronal differentiation (Bormuth et al , 2013; Kepecs & Fishell, 2014), were present in subpopulations of MGE and PFC, respectively (Figs 1C and EV1F). In contrast, other regional identity genes, such as EN1 and TAL2 for midbrain (Metzakopian et al , 2012), VAX1 for hypothalamus (Hallonet et al , 1998; Wang et al , 2015), and GSX2 , HTR3A , and EBF1 for lateral/caudal ganglionic eminences (LGE/CGE) (Kepecs & Fishell, 2014; Mayer et al , 2018), were not detected (Fig EV1G).…”
Section: Resultsmentioning
confidence: 98%